Parameter Demografi Simpai (Presbytis melalophos) di Taman Hutan Raya Sultan Thaha Syaifuddin Jambi: Demographic parameters of simpai (Presbytis melalophos) in Sultan Thaha Syaifuddin Grand Forest Park Jambi - Wulan, Cory; Rifanda, Mahardhika; Rahmilija, Femei; Nahlunnisa, Hafizah; Darsono, Beti Septiana (Fakultas Kehutanan Universitas Jambi, 2024)
Simpai (Presbytis melalophos) are one of protected primate species in Indonesia. This species listed as endangered on the IUCN Red List, indicating a significant risk of extinction in the foreseeable future. This species faces severe threats due to habitat loss from forest area conversion, increasing forest fires, and illegal logging. This study investigates key demographic parameters of the simpai population within Sultan Thaha Syaifuddin Grand Forest Park in Jambi, Sumatra, aiming to provide valuable data for local conservation efforts. The research was conducted from March to April 2022 using purposive sampling method with a total of 4 transects, each measuring 500 m x 20 m. Demographic parameters assessed include population size, density, age structure, and sex ratio. Results indicate an estimated simpai population density ranging from 318 to 1,053 individuals per km², with an average density of 9 individuals per hectare. Age structure analysis shows a predominance of young individuals, with 74 young, 63 adults, and 24 juveniles recorded, while the adult sex ratio is approximately 1:1,36, consisting of 58 males and 79 females